1998
DOI: 10.1002/(sici)1097-4547(19981201)54:5<698::aid-jnr15>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophic and neuroprotective effects of pituitary adenylate cyclase-activating polypeptide (pACAP) on mesencephalic dopaminergic neurons

Abstract: The neuropeptide pituitary adenylate cyclase-activating polypeptide (PACAP) is present in many regions of the adult and developing brain as are receptors for PACAP. PACAP stimulates different signalling cascades in neurons, involving cAMP, MAP kinase, and calcium. These characteristics suggest that PACAP may influence neuronal development. Here we have studied the effects of PACAP on mesencephalic dopaminergic neurons using primary cultures from embryonic rats. PACAP increased the number of tyrosine hydroxylas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(45 citation statements)
references
References 32 publications
2
43
0
Order By: Relevance
“…The density backward declines and the smallest number of such fibers is observed in descending colon. It suggests that the exact functions of PACAP in canine digestive tract under physiological conditions are different in particular segments of intestines, what is in agreement with previous studies on other species (19,29,30).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The density backward declines and the smallest number of such fibers is observed in descending colon. It suggests that the exact functions of PACAP in canine digestive tract under physiological conditions are different in particular segments of intestines, what is in agreement with previous studies on other species (19,29,30).…”
Section: Discussionsupporting
confidence: 91%
“…As a result they confirm previous studies, where expression of PACAP has been described in the GI tract of various species, including humans (8,10,14,19,20), and suggest that also in dog this peptide plays, known in other species, important multiple biological functions for optimal functioning of the gastrointestinal tract. Its role has been shown in processes, such as the gut motility, regulation of neurotransmitter release, as well as secretion of the gastric and intestinal glands (6,19,29,30). On the other hand, in spite of the fact of well-established function of PACAP in the GI tract (19), the number of the enteric PACAP-27-LI neurons under physiological conditions generally noted in the study was relatively low, especially in small and large intestine, what confirms previous studies, which demonstrated that PACAP is the predominant form in mammalian tissues (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, PACAP38 can attenuate neuronal damage from 6-hydroxydopamine (6-OHDA), a Parkinson's disease model toxicant, when administered to primary mesencephalic cultures or co-infused into the substantia nigra of adult rats (Takei, et al 1998, Reglodi, et al 2004b). Since PACAP38 has been shown to be neuroprotective against 6-OHDA, we decided to examine the effects of PACAP38 on the neurotoxicity of systemically-administered methamphetamine (METH).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the actions of PACAP on cortical neurons are mediated through the cAMP pathway (Martin et al, 1995;Morio et al, 1996) although it has been reported that PACAP can directly modulate N-methyl-D-aspartate receptors independently of intracellular second messengers (Liu and Madsen, 1997). In cortical neurons, PACAP can also prevent the neurotoxic effect of other insults such as lipopolysaccharide (Kong et al, 1999), and in mesencephalic dopaminergic neurons PACAP can counteract the neurotoxic effect of 6-hydroxydopamine (Takei et al, 1998). In a study relevant to AD, it was shown that PACAP can protect PC12 cells against death induced by amyloid β-peptide (Onoue et al, 2002).…”
Section: Pituitary Adenylate Cyclase Activating Peptide (Pacap)mentioning
confidence: 99%